Efficacy of neoadjuvant platinum-based chemotherapy during the second and third trimester of pregnancy in women with cervical cancer: an updated systematic review and meta-analysis - Song Y; Liu Y; Lin M; Sheng B; Zhu X (Dove Medical Press, 2018)
Yizuo Song, Yi Liu, Min Lin, Bo Sheng, Xueqiong Zhu Department of Obstetrics and Gynecology, The Second Affiliated Hospital of Wenzhou Medical University, Wenzhou 325027, China Purpose: To evaluate the efficacy and safety of neoadjuvant platinum-based chemotherapy during pregnancy in women with cervical cancer. Methods: The PubMed, Embase, and Cochrane Library databases were fully searched to find eligible studies regarding platinum use during pregnancy in women with cervical cancer from January 1980 to September 2018. Data were extracted from the selected studies independently by two authors. Descriptive statistics were calculated for categorical data (frequency and percentage) and numeration data (mean and SD for normally distributed data and median and range for abnormally distributed data). Survival analyses were performed using Kaplan–Meier survival curves and log-rank tests to estimate overall survival and progression-free survival for all patients. Results: A total of 39 studies including 88 cervical cancer patients with platinum administration during pregnancy were selected in this meta-analysis, and 64 women provided International Federation of Gynecology and Obstetrics stage information. Among the latter, 56 of 64 (87.5%) were diagnosed with early stages (I and IIA) and the remaining 8 of 64 (12.5%) had advanced stages (IIB, III, and IV). In relation to cisplatin, 86 pregnant women were identified, whereas only 2 pregnant women with carboplatin application were retrieved. Overall, 88 newborns were delivered from 84 pregnancies, including two sets of twins and one set of triplets, among which 71 neonates (71 of 88, 80.7%) were completely healthy at birth. All children were healthy at the end of follow-up (median 17 months, range 0–149.5 months), except one who was diagnosed with retroperitoneal embryonal rhabdomyosarcoma at 5 years old and one who had acute myeloid leukemia at 22 months of age. At the end of follow-up (range 4.75–156 months), 16 of 81 (19.8%) patients were diagnosed with recurrence of cervical cancer, and 11 (90%) of those died because of cancer relapse. Neither median overall survival nor median progression-free survival were reached. Conclusion: Our results demonstrated that neoadjuvant platinum-based chemotherapy could be a favorable choice for the management of patients with cervical cancer during the second and third trimesters. To reduce the side effects of chemotherapy, cisplatin might be good to use as monotherapy in these patients. Keywords: platinum, neoadjuvant chemotherapy, pregnancy, cervical cancer, meta-analysis